(untitled) (Colloquia Comparativa Litterarum, 2025)
Olena Berezovska Picciocchi. The Corsican Mazzeru and the Carpathian Molfar: Ancient Characters of European Legends. Preface by Karin Ueltschi-Courchinoux. Riveneuve, 2019.